ANALISIS MANAJEMEN SUMBER DAYA INSANI PADA KOPERASI GUNA MENCAPAI KEMANDIRIAN EKONOMI PONDOK PESANTREN - AL QORNI, FARID ILHAM; Herachwati, Nuri; Rofiki, Akhmad; Muhtadi, Ridan (LP2M IAI Miftahul Ulum Pamekasan, 2022)
The development of a business is very necessary for a skilled, highly motivated, innovative and experienced workforce or human resources, but based on field conditions, it shows that the development of human resources in the Pondok Pasantren Miftahul Ulum Palengaan Cooperative, Pamekasan is still less consistent. This can be seen from employees who lack the ability to manage their human resources so that problems arise, namely the lack of effectiveness of development, especially in terms of economics. The research in this article uses the type of field research that describes the phenomena that occur according to the conditions in the field conducted by searching for data directly in the field. The research method used is a qualitative approach through interviews, observation, and documentation. The results of this study can be concluded that: (1) there are several roles of the MSDI function that we can do in advancing the development of this pasantren cottage cooperative, especially in Human Resource Management such as the functions of planning, organizing, directing, controlling, procurement, development, integrating, compensation, maintenance and discipline (2) there are inhibiting factors, namely SDI that is less qualified and many cooperatives or shops engaged in the same sector. and there are supporting factors in the form of a high sense of enthusiasm between administrators and members and there is a development of santri ideas and innovations through the Santripreneur program that can develop Pasantren cooperatives in empowering economic independence at Pasantren Miftahul Ulum Pamekasan.Keywords: Management, Insani Resources, Economic Independence